2018
DOI: 10.1021/jacs.8b06442
|View full text |Cite
|
Sign up to set email alerts
|

Rational Engineering of a Designed Protein Cage for siRNA Delivery

Abstract: Oligonucleotide therapeutics have transformative potential in modern medicine but are poor drug candidates in themselves unless fitted with compensatory carrier systems. We describe a simple approach to transform a designed porous protein cage into a nucleic acid delivery vehicle. By introducing arginine mutations to the lumenal surface, a positively supercharged capsule is created, which can encapsidate oligonucleotides in vitro with high binding affinity. We demonstrate that the siRNA-loaded cage is taken up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(148 citation statements)
references
References 56 publications
2
134
0
Order By: Relevance
“…9), which also revealed that Nile Red was distributed throughout the cell. Based on the intracellular trafficking of OP cages, the majority of which localize in endosomes 22 , this result suggests that the Nile Red cargo escapes from the capsids after internalization and shuttles to hydrophobic environments in the cell. To test this hypothesis, Atto425-labeled OP capsids were used ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…9), which also revealed that Nile Red was distributed throughout the cell. Based on the intracellular trafficking of OP cages, the majority of which localize in endosomes 22 , this result suggests that the Nile Red cargo escapes from the capsids after internalization and shuttles to hydrophobic environments in the cell. To test this hypothesis, Atto425-labeled OP capsids were used ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Another study used the octahedral cages as a starting point and introduced positively charged amino acids to facilitate siRNA uptake. Interestingly, these containers were able to deliver their cargo to mammalian cells and induce RNA interference (RNAi) and knockdown gene expression . Overall, artificial protein containers are a promising scaffold for delivery applications and material design.…”
Section: Novel Protein Architecturesmentioning
confidence: 99%
“…Protein-based nanoparticles, both natural and designed, have gained increasing attention as promising materials for a wide variety of applications in nanotechnology, nanomedicine, and materials science. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The growing interest in proteinbased materials has stimulated interest in designing new protein assemblies of various architectures that incorporate structural and functional properties that extend beyond those found in Nature. The assembly of protein building blocks (PBB) into large-scale cage-like structures has been accomplished through different approaches; these include the design of new protein-protein interfaces, [16][17][18] the fusion of oligomeric protein domains, 19,20 and by using de novo-designed oligomeric coiled coils to connect together larger, natural proteins.…”
Section: Introductionmentioning
confidence: 99%